Analisis Work Life Balance, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada Bank Kalbar Cabang Semitau - Andre Renaldi (MABIS, 2025)
The purpose of this study is to develop a conceptual model to examine the relationship between Work-Life Balance, Job Satisfaction, and Work Motivation variables and Employee Performance at Bank Kalbar, Semitau Branch. This study employed an associative method. A questionnaire was used as the data collection technique. The analysis method used was multiple linear regression, processed by computer using Statistical Product and Service Solutions (SPSS) version 26. Data were tested using validity, reliability, classical assumptions (normality, linearity, multicollinearity, and heteroscedasticity), coefficient of determination, multiple linear regression, F-test, and t-test. The results indicate that Work-Life Balance, Job Satisfaction, and Work Motivation simultaneously influence Employee Performance.